Assessment of Ductile Failure Models in Single-Pass Wire Drawing Processes - Cruchaga-Ssa., M; Gonzalez-Ortega, A (SAGE Publications Ltd, 2018)
The present work reports a comparative study of ductile failure models applied to an Al-2011 aluminum alloy single-pass wire drawing process using different reductions. The material damage experienced in the wire after passing through the die is evaluated using the well-known Rice and Tracey, Cockcroft and Latham, Brozzo and Modified Chaouadi models. Due to the fact that nonrealistic damage predictions are found for the highest studied wire reduction, an alternative uncoupled failure criterion combining the effect of deformation and triaxility is proposed. The ability of these five models in predicting the formation of chevrons in the process is the main focus of this research. First, the model parameters are characterized by means of numerical simulations of the tensile test. Then, the predictions of the numerical analyses of the drawing process are compared with available experimental results where physical evidence of chevrons was found. Relevant variables are analyzed to determine their incidence in the formation of central bursts. Finally, the performance of this new model is assessed for the full reduction scenarios. © The Author(s) 2017.